Study on DEM Correction Method of Digital Twin Basic Data Baseboard - HONG Minghai; YAN Tao; LIU Hui; WANG Xingjian; JING Na; WANG Shiwei; WEI Wenjie; LI Xinan; FENG Chuqiao (Renmin Zhujiang)
DEM is one of the most important digital twin basic data and has played a huge role in water conservancy planning,design,and engineering construction.However,the existence of various DEM errors greatly reduces the credibility of analysis and application results.In particular,the missing value after terrain conversion to DEM greatly limits subsequent DEM-based analysis.Based on the principle of raster calculation,this paper calls the corresponding tool of ArcGIS by Python to correct the missing value at the overlapped area of a certain terrain converted to DEM by using the mean of eight valued pixels around the pixel.The results show that the calculation method is highly applicable,reliable,and fast.The data of the corrected and compared values of 306 NoData pixels in the study area are close to the 1∶1 line;the maximum difference between the corrected and compared values is only 3.55 m,and the medium error value is 0.75,which is far below the standard error limit.Calling Numpy through Python greatly improves the calculation speed (10 s),and ArcGIS currently has no tool for directly correcting this method.In contrast,the DEM correction method proposed in this paper can be processed in batch,without processing failures due to memory limit,which greatly improves the work efficiency and has a strong application value for processing digital twin basic data.